2012
DOI: 10.1111/j.1365-2672.2012.05396.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of egg yolk immunoglobulin (IgY) against periodontal disease-causing Fusobacterium nucleatum

Abstract: Aims To evaluate the in vitro and in vivo effectiveness of egg yolk immunoglobulin (IgY) against periodontal disease‐causing Fusobacterium nucleatum. Methods and Results Four White Leghorn hens (120 days old) were immunized with whole Fus. nucleatum cells killed with 1% formaldehyde using three injections provided at 2‐week intervals. IgY was produced from egg yolks obtained from these immunized hens using water dilution, two‐step salt precipitation and ultrafiltration. This IgY was shown to have a purity of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
0
18
0
2
Order By: Relevance
“…Additionally, studies have shown inhibitory growth effect of therapeutic IgY produced against Fusobacterium nucleatum in liquid medium and in the formation of biofilm in polyestyrene plates. Anti-F. nucleatum IgY also reduced bone loss in mice with periodontal disease when applied after the infection, thus presenting therapeutic function [69].…”
Section: Antibacterial Activitymentioning
confidence: 97%
“…Additionally, studies have shown inhibitory growth effect of therapeutic IgY produced against Fusobacterium nucleatum in liquid medium and in the formation of biofilm in polyestyrene plates. Anti-F. nucleatum IgY also reduced bone loss in mice with periodontal disease when applied after the infection, thus presenting therapeutic function [69].…”
Section: Antibacterial Activitymentioning
confidence: 97%
“…nucleatum (Xu et al . ). The binding of IgY on bacteria may block or impair the functions of growth‐related bacterial components and consequently lead to bacterial growth inhibition.…”
Section: Discussionmentioning
confidence: 97%
“…Alveolar bone loss is a common symptom of periodontal disease. Xu et al (2012) reported that Fus. nucleatuminfected mice showed a marked decrease in alveolar bone loss after treated with IgY specific to Fus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations